2016
DOI: 10.1016/j.molmed.2015.11.004
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Eradication: Early Trials (and Tribulations)

Abstract: Antiretroviral therapy (ART) has rendered HIV-1 infection a manageable illness for those with access to treatment. However, ART does not lead to viral eradication due to the persistence of replication-competent, unexpressed proviruses in long-lived cellular reservoirs. The potential for long-term drug toxicities and the lack of access to ART for most people living with HIV-1 infection have fueled scientific interest in understanding the nature of this latent reservoir. Exploration of HIV-1 persistence at the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
90
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(90 citation statements)
references
References 106 publications
0
90
0
Order By: Relevance
“…Here, we report optimized methods that enable sensitive and rapid detection of subfemtomolar cell-associated HIV gag p24 protein in HIV-infected CD4 + T cells from ART-suppressed individuals. Quantifying very small amounts of cell-associated viral antigen produced by low numbers of cells from aviremic/low-reservoir HIV + individuals is an important advancement, as viral protein expression is believed to contribute to tissue inflammation and persistent immune activation, and induction is a prerequisite for several investigational immune-mediated "kill" strategies (3)(4)(5)40). The assay can be completed in approximately 1 hour, typically requires 1-2 million peripheral CD4 + T cells from ART-suppressed HIV + individuals, and can be applied to quantify viral protein in cell lysates or culture medium.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Here, we report optimized methods that enable sensitive and rapid detection of subfemtomolar cell-associated HIV gag p24 protein in HIV-infected CD4 + T cells from ART-suppressed individuals. Quantifying very small amounts of cell-associated viral antigen produced by low numbers of cells from aviremic/low-reservoir HIV + individuals is an important advancement, as viral protein expression is believed to contribute to tissue inflammation and persistent immune activation, and induction is a prerequisite for several investigational immune-mediated "kill" strategies (3)(4)(5)40). The assay can be completed in approximately 1 hour, typically requires 1-2 million peripheral CD4 + T cells from ART-suppressed HIV + individuals, and can be applied to quantify viral protein in cell lysates or culture medium.…”
Section: Discussionmentioning
confidence: 99%
“…To eliminate the latent reservoir, infected cells must be recognized as harboring virus and then effectively destroyed and cleared. Latency disruption is under intense investigation, and several strategies are being evaluated (3)(4)(5)(6). Recent therapeutic approaches have focused on the use of latency-reversing agents (LRAs) to induce viral transcription, initiate viral translation, and subsequently elicit death through viral cytopathic effects or immune-mediated cell killing ("shock and kill").…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Agents eliciting global T cell activation were used in the original detection of the reservoir (1, 2) and effectively reverse latency. However, in clinical settings they induce severe adverse reactions by causing systemic release of proinflammatory cytokines (6,7). Although clinical trials using T cell-activating agents such as anti-CD3 and IL-2 have demonstrated transient increases in viremia and changes in HIV-1 intracellular RNA levels (6), this approach has been abandoned in favor of latency-reversing agents (LRAs) that induce HIV-1 transcription without cellular activation.…”
Section: Integrated Proviruses In Resting Cd4mentioning
confidence: 99%
“…Current strategies to eliminate latent reservoirs, such as shock and kill, employ the use of latency reversing agents (LRAs) such as the PKC agonist Bryostatin-1 or histone deacetylase inhibitors (HDACi) romidepsin and panobinostat to induce virus production from latently infected cells in order to facili-tate their elimination by various mechanisms such as viral cytopathic effects or CD8 T cell-mediated clearance (62). However, to our knowledge, no single intervention to date has resulted in a significant reduction of the viral reservoir in vivo while various adverse effects have been observed (62,63).…”
Section: Discussionmentioning
confidence: 99%